Pengaruh Promosi Instagram Terhadap Keputusan Penggunaan Jasa MUA pada Mahasiswa Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang (International Forum of Researchers and Lecturers, 2024)
Instagram promotion is an effective way to influence consumers in making purchase decisions. The strategy used is to make the context of the advertisement as attractive as possible so that consumers are interested in using the product/service being marketed. This study aims to analyze Instagram promotion in FPP UNP students, analyze the decision to use MUA services in FPP UNP students, analyze the influence of Instagram promotion on the decision to use MUA services in FPP UNP students. This type of research is causal associative with a quantitative method approach. The population of this study is 400 FPP UNP students class of 2020. Sampling using the purposive sampling technique totaled 80 respondents. The data collection technique using a questionnaire was made through a google form and measured using a likert scale that has been tested for validity and reliability. The data analysis techniques of this research are data metabolization and data description. The analysis requirements tests carried out are normality tests, homogeneity tests, linearity tests and t-tests for hypothesis testing. Based on the results of the study, it is known that 1) Instagram promotion for FPP UNP students shows that overall with a percentage of 84.14% is in the range of 80-89%. 2) The decision to use MUA services for FPP UNP students shows overall with a percentage of 73.5% in the value range of 67-79% with the medium category. 3) There is an influence of Instagram promotion on the decision to use MUA services for FPP UNP students. The Instagram promotion variable has a partial influence of 25.2% on the decision to use MUA services while 74.8% is influenced by other variables that are not examined in this study.